Pichia Toolkit: Use of the combinatorial library screening system for expression of a marine laccase - Otero, Igor Vinicius Ramos [UNESP]; Haslbeck, Magdalena; Sieber, Volker; Sette, Lara Durães [UNESP] (Springer Nature, 2025)
Pnh_Lac1 (Lac1) gene from the marine-derived fungus Peniophora sp. CBMAI 1063 was expressed in Pichia pastoris using the Pichia Toolkit system. Constitutive (pGAP, pPET9, pG1, pG6, and pADH2) and methanol-inducible (pAOX1, pDAS1, and pPMP20) promoters were assessed in combination with 21 different signal peptides and His-tag about efficiency in laccase production. Next, 3,200 variants were screened, different culture conditions were evaluated, and an investigation was performed in a bench-scale bioreactor for the best variant selected. The influence of promoters and signal peptides on Lac1 expression was demonstrated in the constitutive libraries. The change from pG6 to pGAP resulted in a 171-fold increase in production. Changing the alpha-mating factor peptide by the native signal peptide of the Lac1 gene decreased laccase production 22-fold. The promoters pGAP (constitutive library) and pAOX1 (inductive library) performed best. The association with the signal peptide αAmylase-αMFD was more efficient for both promoters. The constitutive expression of Lac1 had a 1.37-fold greater production compared to the inducible expression achieved by pAOX1 and was considered more suitable for laccase expression. Culturing the best producer variant pGAP_αA1 at pH 6 and 18 °C resulted in the best production rate in deep-well plates (90 U/L). Constitutive laccase production in a 2-L bioreactor resulted in a peak production of 178 U/L after 78 h. Pichia Toolkit was efficient in the selection of the best molecular regulation and secretion of Lac1. Our findings contribute to the development of marine biotechnology and will serve as the basis for Lac1 production optimization.